Concept of human rights - "Donnelly, Jack" (London, 1985)
Donnelly distinguishes between "having a right" and "being right" and elaborates the distinction with great subtlety to show that rights have to be understood as action and not as a possession. This is done with such clarity and good sense that he is able to cast light on all aspects of the often confusing discussions of the natures and usages of "right". He illuminates an astonishing range of issues, from the limitations of Thomist and utilitarian conceptions of right to the confusions of many present-day defenders of rights, both in the West and the Third World. As importantly, Donnelly is centrally concerned with the human aspect of "human rights". He is thus able to rest his discussion of rights on a plausible philosophical anthropology as well as an appreciation of an historical dimension to human rights, and, at the end of his book, is able to open the door towards potential new developments in the discussion of human rights. Down the path he points us lies a reconciliation of the notion of individual rights with that of political community. This title will be of great interest to students of politics and philosophy.
Keywords: Civil rights